Citogenética de acessos de Cratylia sp. (FABACEAE - PAPILIONOIDEAE) - Vargas, Sarah Maria (2005)
Cratylia argentea and Cratylia mollis are legumes shrubs native from Cerrado and Caatinga respectively. Both show great drought resistance and hight nutritive value. Cytogenetics and morphological studies were carried out on 10 acessions of Cratylia argentea and 1 of Cratylia mollis, belonging of EMBRAPA Germplasm Bank of Gado de Leite - Juiz de Fora MG and Semiárido - Petrolina PE, respectivly. For each one of these accessions a description of the cromossomic complement was performed considering the following features: chromosome number, total chromosome length (Cti), arm ratio (A), relative length (CR) and total haploid set length (CTLH). Root tips from germinated seeds were treated with 8-Hidroxiquinolein to provide metaphasic figures. The cell walls of meristematic cells were softened using PectinexÒ and the slides were made using air-dry technique. In meiotic analysis, flower buds showing distinct sizes were submitted to air-dry technique. Mitotic methaphases in all acessions showed 2n= 22 chromosomes and meiotic diakinesis resented 11 bivalents for C. argentea. For these species, this is the first report about chromosome number. Statistical analysis for CTHL and CR features showed that there is no difference among the accessions of C. argentea nor among them and C. mollis. In regard to chromosomes morphology, C. argentea presented 5 metacentric pairs, 4 submetacentrics and 2 acrocentrics. On the other hand, C. mollis presented 6 metacentric pair, 3 submetacentrics and 2 acrocentrics. Morphometric analysis showed that both species have quite similar karyotypes. Only morphology of chromosomes I, IV and VI were clearly differente. This cytogenetic approach suggests us the hypothesis that we are dealing with just one species.